2020
DOI: 10.3847/2041-8213/ab83fa
|View full text |Cite
|
Sign up to set email alerts
|

A White-light Flare Powered by Magnetic Reconnection in the Lower Solar Atmosphere

Abstract: White-light flares (WLFs), first observed in 1859, refer to a type of solar flares showing an obvious enhancement of the visible continuum emission. This type of enhancement often occurs in most energetic flares, and is usually interpreted as a consequence of efficient heating in the lower solar atmosphere through non-thermal electrons propagating downward from the energy release site in the corona. However, this coronal-reconnection model has difficulty in explaining the recently discovered small WLFs. Here w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The low solar atmosphere is naturally a good laboratory for providing suitable opportunities to study magnetic reconnection in partially ionized plasma. Numerous small-scale events of reconnection in the low solar atmosphere have been observed in multi-wavelengths by advanced solar telescopes of high resolution and the fine structures of these events have also been recognized (e.g., Peter et al 2014;Xue et al 2016;Tian et al 2018;Huang et al 2018;Romano et al 2019;da Silva Santos et al 2020;Yan et al 2020;Song et al 2020;Joshi et al 2021;Rast et al 2021;Hou et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The low solar atmosphere is naturally a good laboratory for providing suitable opportunities to study magnetic reconnection in partially ionized plasma. Numerous small-scale events of reconnection in the low solar atmosphere have been observed in multi-wavelengths by advanced solar telescopes of high resolution and the fine structures of these events have also been recognized (e.g., Peter et al 2014;Xue et al 2016;Tian et al 2018;Huang et al 2018;Romano et al 2019;da Silva Santos et al 2020;Yan et al 2020;Song et al 2020;Joshi et al 2021;Rast et al 2021;Hou et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With observations of the Interface Region Imaging Spectragraph (IRIS, De Pontieu et al 2014), Peter et al (2014) identified four UV bursts (UBs) and suggested that they might be produced by magnetic reconnection in U-shape structures during flux emergence in the lower solar atmosphere. Subsequent studies revealed that these UBs indeed mostly occur in emerging flux regions (e.g., Vissers et al 2015;Tian et al 2016Tian et al , 2018bNelson et al 2016;Young et al 2018;Chen et al 2019c) and that some of them are indeed associated with U-shape magnetic field structures (e.g., Grubecka et al 2016;Zhao et al 2017;Tian et al 2018a;Chen et al 2019b;Song et al 2020). The difference is that EBs and UBs are more likely related to magnetic reconnection occurring in the lower-atmosphere part of the U-shape structures, whereas the reconnection in our observations appears to occur in a relatively higher part (possibly the lower corona) of the U-shape structures.…”
Section: Discussionmentioning
confidence: 99%
“…The code has also been applied to study solar activities in the lower atmosphere such as Hα fibrils (Zhu et al 2016), small-scale filament (Wang et al 2016), ultraviolet burst (Zhao et al 2017;Tian et al 2018;Chen et al 2019), and blowout jet (Zhu et al 2017). Other applications focus on large-scale structures of the magnetic fields in the corona also show the robustness of the method (Song et al 2018;Miao et al 2018;Joshi et al 2019;Song et al 2020;Fu et al 2020).…”
Section: Mhd Relaxation Methodsmentioning
confidence: 99%